1994
DOI: 10.1017/s0022112094000492
|View full text |Cite
|
Sign up to set email alerts
|

Pressure fluctuations and their effect on cavitation inception within water jets

Abstract: Instantaneous and phase averaged pressure distributions in the near field of a jet, and their effects on the conditions for the onset of cavitation are studied in detail. The measurements are performed by using microscopic bubbles as pressure sensors, and holography as a means of detecting them. Experiments are performed at Red exceeding 4 × 105, with and without acoustic excitation. The results show that the highest negative pressure peaks (–0.97) and the resulting cavitation inception occur because of vortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 14 publications
3
31
0
Order By: Relevance
“…The resulting cavitation inception location can occur at random sites throughout the shear layer. [2][3][4] Similar observations have been made in jets 5,6 and in the wake of cavitating wedges. 7 In propellers for marine applications, tip vortex cavitation is generally the first form of cavitation to be observed.…”
Section: Introductionsupporting
confidence: 75%
“…The resulting cavitation inception location can occur at random sites throughout the shear layer. [2][3][4] Similar observations have been made in jets 5,6 and in the wake of cavitating wedges. 7 In propellers for marine applications, tip vortex cavitation is generally the first form of cavitation to be observed.…”
Section: Introductionsupporting
confidence: 75%
“…It puts forward the main ingredients for turbulence-induced inception: That the cavitation nuclei are subject to pressure fluctuations as measured in a Lagrangian frame, and that (a) the pressure must dip below a critical level (p cav , the cavitation pressure, also called Blake threshold 11 ), and (b) the low pressure must persist below the critical level for a time that exceeds the time scale for bubble growth. The picture has been confirmed and enriched over the years by several authors [12][13][14][15] , including the role of coherent structures and the possibility of using incip-ient cavitation bubbles as pressure sensors.…”
Section: Introductionmentioning
confidence: 70%
“…The pressure PDF in HIT is known to be negatively skewed and exhibit an exponential tail at very low pressures [2][3][4] .On the basis of physical intuition, several authors have argued that the frequency ζ(δp) of pressure fluctuations below δp should also exhibit an exponential tail for large and negative δp 10,12,14 . Mathematically, this is far from obvious.…”
Section: Introductionmentioning
confidence: 99%
“…Kudirka and Decoster (1979) found that the vapor bubble firstly occurred inside the jet boundary in CJP. Then, Ran and Katz (1994) validated that the cavitation inception appeared at the vortex center of the jet, which was related to the fluctuation of the shearing layer, and it will also form in the vortex center of the co-flow with the cavitation nuclei growing. Hence the inception of cavitation in CJP can be due to high shear and vortex in jet boundary (namely shearing layer).…”
Section: Introductionmentioning
confidence: 81%